Factors that influence customer preferencestowards a private university inSungai Petani, Kedah / Azyyati Anuar, Mohd Rizaimy Shaharudin and Siti Nabihan Baharuddin - Anuar, Azyyati; Shaharudin, Mohd Rizaimy; Baharuddin, Siti Nabihan (Universiti Teknologi MARA, Kedah, 2011)
This study attempts to focus on the factors influencing customer preferences towards a private university in Sungai Petani, Kedah. Nowadays, demand for higher education in Malaysia is growing in tandem with the government's emphasis on human capital development. Without private higher education, hundreds of thousands of students would have difficulties of gaining the knowledge as places in public universities are limited. The research aims to identify factors such as image and reputation, quality of education and overall cost of education that influence customer's choice and preference in choosing future higher educational institute. A sample of 200 students from secondary schools participated in this study. Data collected from the questionnaires were analyzed by using regression analysis to determine the relationship between dependent and independent variables. Results from the study shows that the quality of education and overall cost of education significantly influenced the customer preferences. Future research should also focus on the factors studied or even other factors that influence customer preferences by enlarging the scope to include all private universities and colleges in Malaysia. Additional variables such as administration, facilities, lecturers or programme offered of private or public universities can be further examined to increase the accuracies and effectiveness of the findings.